Initial understory vegetation responses following different forest management intensities in Illyrian beech forests. Issue 1 (6th February 2019) - Kermavnar, Janez; Eler, Klemen; Marinšek, Aleksander; Kutnar, Lado
Abstract: Background and questions: How forest vegetation responds to disturbance continues to be a focal point, especially in the context of biodiversity conservation. To investigate the short‐term effects of forest management on understory vegetation, we asked: (a) Are there any plant indicator species associated with different felling intensities? (b) What are the differences in abundance of plant functional types along the disturbance gradient? (c) How do typical forest species respond to silvicultural treatments? Location: Dinaric Mountains, Slovenia. Methods: At each of three study sites in Illyrian beech forests, nine plots (4, 000 m 2 ) were established, comprising a total of 27 plots. Three different felling intensities were implemented at each site, with one third of the plots assigned to each treatment: control, 50% of the growing stock removed and 100% of the growing stock removed. In the centre of each plot, a vegetation survey of vascular plants was done before (in 2012) and two years after (in 2014) felling in a circular sampling area of 400 m 2 . We employed indicator species analysis, and species were grouped into functional types with respect to their traits. Results: Understory species composition differed significantly between treatments. Forty‐seven species (out of 251) were significantly associated with the 100% felling intensity. This relatively high number of indicators was due to the post‐disturbance colonization of early‐successional, non‐forest species, coupled with the expansion of pre‐treatment resident species. Only one species was a strong indicator for the 50% felled plots, while three species showed a preference for the unfelled plots. Graminoids, tall perennial forbs, annual/biennial forbs and legumes exhibited the most prominent increase in cover at the 50% and 100% felling intensity. Ferns showed non‐significant changes, whereas woody plants exhibited a decrease in the most intensive treatment. In general, most of the typical forest species responded with increased frequency and/or abundance after felling. Conclusions: The post‐treatment taxonomic and functional composition of plant communities exhibited the largest changes in the most intensively felled stands. Overall, in the short term, ecological conditions in canopy gaps were not modified to an extent that would be detrimental to the persistence of typical forest species. Abstract : We investigated the short‐term effects of different forest management intensities on understory vegetation in Illyrian beech forests. The post‐treatment taxonomic and functional composition of plant communities exhibited the largest changes in the most intensively felled stands, which were driven by colonization of non‐forest species. The resistance of typical forest plant species largely contributed to the short‐term compositional stability of the understory vegetation.